Individualized total laparoscopic surgery based on 3D remodeling for portal hypertension: A single surgical team experience - YIN, JiKai; Wang, Dong; Zhang, Li; Dong, Rui; Yang, Tao; Huang, Bo; Sun, Yibo; Lei, Shixiong; Qiangshan, Bai; Lu, Jianguo (Frontiers in Surgery, 2022)
Background and aims: Portal hypertension (PHT) is common in end-stage cirrhosis, and variceal bleeding is the main complication associated with mortality. Surgery is usually performed in patients with PHT with a high risk of variceal bleeding in China. This study aimed to introduce an individualized and precise total laparoscopic surgical procedure based on 3D remodeling for PHT. Methods: From March 2013 to December 2018, 146 patients with cirrhotic PHT underwent a novel laparoscopic surgical procedure in our department. An individualized 3D remodeling evaluation was carried out for surgical planning. Results: The operation time was 319.96±91.53 minutes. Eight of 146 patients were converted to open surgery. Acute portal vein system thrombosis occurred in 10 patients (6.85%). During the first year, 11 patients (8.15%) experienced rebleeding and two (1.48%) died. 18 patients (13.33%) experienced rebleeding and three died, giving a 3-year mortality rate of 3.66%. Compared with preoperatively, the portal vein showed significant postoperative decreases in diameter, flow velocity, and flow amount, while the hepatic artery showed significant postoperative increases in diameter, flow velocity, and flow amount. A 3D liver volume evaluation found that 19 of 21 patients had a significantly increased liver volume postoperatively, and a significantly decreased MELD score. Conclusion: This retrospective study introduced a safe, feasible, and effective individualized surgical procedure. Our results show that this surgical treatment may not only act as an effective symptomatic treatment for PHT to prevent esophageal and gastric hemorrhage, but also as an etiological treatment to increase liver function and long-term survival.